Determining The Best Coffee Menu Using AHP Method On Khobu Coffee - Dio Arif Pranoto; Miftahul Jannah (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
Khobu Coffee is a business unit that sells various coffee menus to its customers every day. The various coffee menus have their characteristics according to the interests of the infringer who buys or orders from the available coffee menu. In fact, in determining the best coffee menu used at Khobu Coffee, based on the survey results, the author has not used a system that can select the best coffee menu based on coffee beans from the menu. Therefore we need a system that can assist in supporting decision-making more quickly, precisely, and accurately. One of them is using the Analytic Hierarchy Process (AHP) method because this method is one method that can perform multiple and detailed criteria with a comprehensive framework and consideration of the hierarchical process which is then calculated for each criterion in determining the best coffee beans. The criteria used are taste, price, aroma, body (thickness level), and acidity (acidity level). The programming language used in building the system is PHP with MySQL. The results of the implementation of the system that has been built show that the AHP method can provide objective decisions in determining the best coffee beans.